2018
DOI: 10.1007/s12024-018-9946-1
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem radiological case series of acetabular fractures after fatal aviation accidents

Abstract: The purpose of this study was to describe radiological fracture patterns of the acetabulum sustained after fatal small aircraft aviation accidents, aiming at facilitating a better understanding of trauma mechanisms in a forensic setting. Postmortem conventional radiographs or CT scans of 29 victims of 20 small aircraft aviation accidents were analyzed for skeletal acetabular trauma. Among the 29 fatalities (27 males and 2 females, median age 55 years (range: 21–76 years)), 20 victims had pelvic fractures (69%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The most common fracture types in our study were ABC, AC, TPW and PW with frequencies similar to those reported in the literature [1, 45,46,[50][51][52]. PWC and T-shaped were the least common, whilst no cases with PC fractures we reported.…”
Section: Discussionsupporting
confidence: 87%
“…The most common fracture types in our study were ABC, AC, TPW and PW with frequencies similar to those reported in the literature [1, 45,46,[50][51][52]. PWC and T-shaped were the least common, whilst no cases with PC fractures we reported.…”
Section: Discussionsupporting
confidence: 87%
“…Few studies are available that report airplane crashes in an archaeological context (Gapert & Rieder, 2013; Palmiotto et al, 2020). Most of these types of studies are reported in forensic literature (Byard & Tsokos, 2006; de Bakker et al, 2018) or consist of recent professional experiences (such as an army helicopter crash in southeast France or previously an airliner crash in the Alps), but patterns observed in soldiers are similar, especially with respect to helicopter accidents. In impact injuries, the compression of the thoracic cavity and ribs causes transverse fracture, and extension of the rachis causing the fracture of the spinous process is often observed.…”
Section: Discussionmentioning
confidence: 99%